1987
DOI: 10.1901/jaba.1987.20-179
|View full text |Cite
|
Sign up to set email alerts
|

Using Intermittent Reinforcement to Program Maintenance of Verbal/Nonverbal Correspondence

Abstract: We investigated the effects of an intermittent reinforcement procedure on maintenance of verbal/nonverbal correspondence with nutritious snack choices in a day-care setting. Nutritious snack choices were first established using correspondence training procedures in a multiple baseline across three children. Withdrawal of the procedures with one subject led to loss of appropriate responding, suggesting the need for a maintenance strategy. The intermittent reinforcement procedure was implemented in a multiple ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
30
0
3

Year Published

1991
1991
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 10 publications
3
30
0
3
Order By: Relevance
“…Thus, in the present programme, once children 'acquire the taste' for the fruits and vegetables, these foods provide their own intrinsic rewards to supplement and, in time, perhaps entirely replace the programme's extrinsic rewards. The effectiveness of the present study's extrinsic rewards in increasing consumption and liking of fruit and vegetables is consistent with the findings of many other studies that have used rewards to alter food consumption and choice (Bernal, 1972;Hatcher, 1979;Siegel, 1982;Riordan et al, 1984;Handen et al, 1986;Stark et al, 1986;Baer et al, 1987;Hendy, 2002;.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Thus, in the present programme, once children 'acquire the taste' for the fruits and vegetables, these foods provide their own intrinsic rewards to supplement and, in time, perhaps entirely replace the programme's extrinsic rewards. The effectiveness of the present study's extrinsic rewards in increasing consumption and liking of fruit and vegetables is consistent with the findings of many other studies that have used rewards to alter food consumption and choice (Bernal, 1972;Hatcher, 1979;Siegel, 1982;Riordan et al, 1984;Handen et al, 1986;Stark et al, 1986;Baer et al, 1987;Hendy, 2002;.…”
Section: Discussionsupporting
confidence: 90%
“…However, there is also a large body of research testifying to the efficacy of rewards (eg see Dickinson, 1989;Cameron et al, 2001). A number of studies, for example, have employed them successfully to encourage food consumption among children with feeding difficulties (Bernal, 1972;Hatcher, 1979;Siegel, 1982;Riordan et al, 1984;Handen et al, 1986) and to increase children's healthy snack choices (Stark et al, 1986;Baer et al, 1987). This evidence indicates that, when used appropriately, rewards can be very effective at altering behaviour such as children's food consumption.…”
Section: Introductionmentioning
confidence: 99%
“…Say-do correspondence was maintained with minimum variability for all the children when consequences for correspondence became intermittent, regardless of the conditions under which saying was produced. The current data extend the research on thinning consequences reported by Baer et al (1987). Moreover, the maintenance shown in the current study may have important implications in applied settings because it demonstrates the maintenance of say-do relation in conditions less dependent of the specific adult's questions about what the subjects would like to do.…”
Section: Discussionsupporting
confidence: 82%
“…Studies focused on maintenance indicate that it is possible to maintain correspondence by simply reinforcing the verbalization (Baer, Blount, Detrich, & Stokes, 1987;Baer, Williams, Osnes, & Stokes, 1984;Guevremont, Osnes, & Stokes, 1986b;Osnes, Grevremont, & Stokes, 1986;Paniagua & Black, 1990;Ward & Stare, 1990;Whitman, Scibak, Butler, Richter, & Johnson, 1982) or through intermittent reinforcement of the correspondence (Baer et aI., 1987) and indiscriminable or almost random contingencies (Guevremont et aI., 1986b). Research into the generalization of say-do correspondence has suggested that a number of variables may be involved in promoting successful generalization (Guevremont et aI., 1986a;Rogers-Warren & Baer, 1976;Whitman et aI., 1982).…”
mentioning
confidence: 99%
“…In addition, reinforcement schedules may increase the likelihood or amount of other characteristics of responding, including resistance to extinction and disinhibition, and may alter the effects of reinforcement magnitude on resistance. Nevertheless, only a few applied studies have examined the PREE (e.g., R. Baer, Blount, Detrich, & Stokes, 1987;Kazdin & Polster, 1973;Koegel & Rincover, 1977), and each contains some potential limitations that prevent clear interpretation of the data (see Lerman, Iwata, Shore, & Kahng, 1996, for a detailed discussion of these problems).…”
Section: Applied Research and Implicationsmentioning
confidence: 99%